Subcortical brain structure and APOE genotype: An analysis of 43, 000 participants from the UK Biobank. (20th December 2022) - Ching, Christopher RK; Thomopoulos, Sophia I; Santhalingam, Vigneshwaran; Gleave, Emma J; Zhu, Alyssa H; Islam, Tasfiya; Abaryan, Zvart; Jahanshad, Neda; Thompson, Paul M
Abstract: Background: Carriers of the ε4 allele of the apolipoprotein (APOE) gene are at higher risk for developing Alzheimer's disease (AD). In individuals with mild cognitive impairment or AD, the ε4 allele is associated with lower hippocampal and amygdala volumes. How ε4 affects brain structure in healthy individuals before AD symptom onset is less clear. APOE ε2 allele carriers may show slower rates of hippocampal volume loss, suggesting protection against AD. In this large‐scale analysis, we plot normative regional brain volume trajectories in adults (45‐82 years) and map regional subcortical volume differences between APOE genotypes. Method: We used FreeSurfer 7.1 to segment average left and right accumbens, amygdala, caudate, hippocampus, pallidum, putamen, thalamus and lateral ventricle volumes from T1‐weighted brain MRI (N=43, 000). Comparisons between APOE genotypes (ε2ε2, n=257; ε2ε3, n=5, 479; ε3ε3, n=26, 016; ε3ε4, n=10, 263; ε4ε4, n=985) were made using linear mixed effect models, correcting for population structure, age, sex, and intracranial volume (ICV) as fixed effects, and site as a random effect. Results were adjusted for multiple comparisons (FDR q<0.05). Nomograms were derived by adjusting subcortical volumes for population structure, ICV, and site then fitting normative quantile regression models based on the standardized residuals for each region stratified by genotype. Result: Nomograms showed similar age‐related trajectories for all APOE genotypes, with smaller gray matter volume and larger ventricle volumes with increasing age. Significantly smaller amygdala and hippocampal volumes were found in ε4ε4 compared to ε3ε4, ε3ε3, and ε2ε3 carriers, and smaller amygdala volumes in ε2ε2 versus ε3ε3 carriers. Smaller accumbens volumes were found in ε4ε4 carriers versus ε2ε3 and ε3ε3, and in ε3ε4 versus ε3ε3 and ε2ε3. Smaller thalamus volumes were found in ε3ε4 versus ε2ε3 and ε3ε3, ε4ε4 carriers had smaller volumes versus ε2ε3 and ε3ε3, and ε2ε2 carriers had smaller volumes versus ε2ε3 and ε3ε3. Conclusion: In this large sample of generally healthy individuals, APOE ε4 allele carriers exhibited lower subcortical volumes compared to those with more neutral AD genetic risk background (ε3ε3). Carriers of ε2ε2 had smaller thalamus and amygdala volumes compared to ε3ε3, suggesting differential effects of AD genetic risk across brain structures known to play a role in AD pathophysiology.